J. S. 밀의 공리주의에서 동기화 문제와 제재 이론 - 류지한; Lyou Jihan (倫理硏究, 2024)
밀의 공리주의는 쾌락주의의 ‘자기 이익 지향성’과 공리의 ‘일반 이익 지향성’ 사이의 긴장에서 비롯되는 이론 내적인 부정합성의 위험을 안고 있다. 밀은 이런 부정합성을 해소하기 위해 제재 이론을 발전시켰다. 그는 벤담의 외적 제재에 더해서 양심에 의한 내적 제재를 주장하였다. 밀은 제재를 통해서 공리의 원리를 따를 실천 동기와 타산적 이유를 강화하고자 하였다. 밀의 쾌락 공리주의에서 제재는 이론 내적인 정합성을 확립하고 이론적 난점인 동기화 문제와 도덕 정당화 문제를 해결하기 위한 이론적·실천적 기제이다. 더 나아가서 밀은 제재가 의무 개념의 일부로서 행위의 옳고 그름과 밀접히 연관되어 있다고 주장하였다. 이 주장은 그의 쾌락 공리주의를 제재 공리주의로 해석할 근거와 더불어 내재주의 이론으로 해석할 여지를 제공한다. 그리고 내재주의적 제재 공리주의는 외재주의적 쾌락 공리주의가 직면한 ‘동기화 부재 문제’와 ‘과도한 제재 문제’를 해소할 수 있으며, ‘동기화 불충분 문제’에 관해서도 진척된 방안을 제시할 수 있다. Mill's hedonistic utilitarianism carries the risk of internal incoherence resulting from the tension between the self-interest disposition of hedonism and the general interest disposition of utility. Mill developed the sanctions theory to resolve this incoherence. In addition to Bentham's external sanctions, he insisted on internal sanctions by conscience. Through sanctions, Mill strengthened the practical motivation and prudential reason to follow the principle of utility. In Mill's hedonistic utilitarianism, sanctions are a theoretical and practical mechanism for establishing internal coherence in the theory and resolving the theoretical problems of motivation and justification about morality. Furthermore, Mill argued that sanctions are part of the concept of duty, closely connected to the rightness or wrongness of an act. This argument provided grounds for interpreting his hedonistic utilitarianism as sanction utilitarianism along with room for viewing it as intenalism, that is a sort of internalist ethical theory. In addition, internalist sanction utilitarianism can solve the ‘problem of absence of motivation’ and the ‘problem of excessive sanctions’ faced by externalist pleasure utilitarianism, and can also present an advanced solution regarding the ‘problem of insufficient motivation’.